Trends in scientific production related to health economy in Colombia (Revista Electrónica Calidad en la Educación Superior, 2025)
Around the world, health systems have prioritized improving the performance and quality of health services through targeted public policies. This has generated the need to reform existing healthcare models in order to improve management and focus on creating healthcare systems that are high quality, safe and efficient. This study aims to summarize the literature related to Health Economics in Colombia through a bibliometric analysis. 103 documents on the subject extracted from Scopus were examined, and indicators were created to identify the progress of scientific creation, the most relevant journals, authors and organizations, the countries with the greatest production, the bibliographic coupling networks, the most relevant terms. used and future lines of research.The results revealed that publications have been occurring since 1975, peaking in 2023. Additionally, 5 clusters were identified that can guide future research by recognizing emerging scientific trends.
Keywords: Health Economics; Economics and Health Care Organizations; Bibliometrics; VOSviewer; Scopus